KIE how to use Corticosteroid and Vitamins to Patients after Cataract Surgery at KMU Madura - Solihah, Riyadatus; Rizal Umar; Finny Sulistinawati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2023)
The main cause (50%) of blindness in Indonesia is cataracts, cataracts are one of the main health problems in the elderly, the only way to overcome blindness due to cataracts is to perform cataract surgery. Cataracts are a common disease that is often suffered by the elderly, cataracts themselves are characterized by cloudiness in the lens of the eye so that it blocks clear vision, based on national data from the 2014-2016 Ministry of Health's rapis assessment of avoidable blindness needs survey, with the target population being the age group Over 50 years it is known that the blindness rate reaches 3% and cataracts is the highest cause of blindness (81%), representatives and association of Indonesian ophthalmologists dr. Aldiana Halim said that in 2017 there were 8 million people with visual impairments. As many as 1.6 million blind people, plus 6.4 million people with moderate to severe visual impairment, of these, 81.2% of visual impairment is caused by cataracts, other causes are reflex and glaucoma or eye disorders related to diabetes. Corticosteroids are natural steroid hormones in humans which are produced by the adrenal cortex gland and function to treat inflammation or autoimmune disorders in the body. the function of this corticosteroid class of drugs is the same as the corticosteroid hormone produced by the body. After cataract surgery, the doctor gives several drugs to the patient to prevent post-surgical complications including infection (given antibiotics for prophylaxis), dry eye syndrome (given artificial tear drops) and to reduce pain (given anti-inflammatories). This community service aims to increase the knowledge of post-cataract surgery patients about how to use corticosteroid eye drops and how long to use corticosteroid eye drops.